2014
DOI: 10.5433/1679-0359.2014v35n4p2077
|View full text |Cite
|
Sign up to set email alerts
|

Milheto em substituição ao milho na dieta de novilhos confinados

Abstract: ResumoObjetivou-se avaliar o desempenho bioeconômico de novilhos alimentados em confinamento com dietas com elevada proporção de concentrado (80%) contendo diferentes níveis de grão de milheto moído em substituição ao grão de milho moído. Foram utilizados 89 novilhos não castrados, mestiços europeu-zebu, com peso médio inicial de 317,8±15,1kg e idade média inicial de dois anos, distribuídos aleatoriamente em dietas com diferentes níveis de substituição do milho pelo milheto (0, 33, 66 e 100%). Os animais foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
6
6
0
2
Order By: Relevance
“…The lack of variation for average daily gain, final body weight, and hot carcass weight between steers fed pearl millet-and corn-based diets (Table 7) was consistent with those observed in other studies (Gonçalves et al, 2010;Silva et al, 2014;Silva et al, 2015); in fact, most studies have demonstrated similar productive performance of animals fed diets containing corn grain and diets containing pearl millet grain. Moreover, the variation in feed conversion reflects the variation in the DM intake with increasing concentration of dietary BMB, which was also reported by Miotto et al (2013).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The lack of variation for average daily gain, final body weight, and hot carcass weight between steers fed pearl millet-and corn-based diets (Table 7) was consistent with those observed in other studies (Gonçalves et al, 2010;Silva et al, 2014;Silva et al, 2015); in fact, most studies have demonstrated similar productive performance of animals fed diets containing corn grain and diets containing pearl millet grain. Moreover, the variation in feed conversion reflects the variation in the DM intake with increasing concentration of dietary BMB, which was also reported by Miotto et al (2013).…”
Section: Discussionsupporting
confidence: 79%
“…These results were partially similar to those found by Silva et al (2012) and Cruz et al (214), who also found increased consumption of NDF. On the other hand, the similar intakes of DM, EE, CP, NDF, and TDN (Table 4) between diets based on corn and pearl millet was consistent with the literature (Gonçalves et al, 2010;Silva et al, 2014), demonstrating similar nutritional potential between these grains.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The suggestion of these authors may be due to the high BMB levels used in diets. It should be noted that the results obtained for the carcass yield were consistent with similar nutritional values and animal performance in diets with corn or millet (HILL et al, 1996;GONÇALVES et al, 2010;SILVA et al, 2014).…”
Section: Resultssupporting
confidence: 74%
“…O peso ao abate não foi influenciado (P>0,05) pelo grão de milheto em substituição ao de milho (Tabela 2), o que foi determinado pelo similar pelo ganho de peso médio diário (1,75; 1,58; 1,75 e 1,56 kg/dia) e similar consumo de matéria seca (2,25; 2,17; 2,30 e 2,23%) para os animais em dietas com rações contendo 0, 33, 66 e 100% de milheto, respectivamente (SILVA et al, 2014). Todavia, os novilhos com predominância genética Aberdeen Angus apresentaram maior (P<0,05) peso ao abate em relação aos com predominância genética Nelore, resultado do maior ganho de peso médio diário (2,10 vs 1,50 kg/dia) para os primeiros.…”
Section: Resultsunclassified